The torpedo effect in Bacillus subtilis: RNase J1 resolves stalled transcription complexes - Šiková, Michaela; Wiedermannová, Jana; Převorovský, Martin; Barvík, Ivan; Sudzinová, Petra; Kofroňová, Olga; Benada, Oldřich; Šanderová, Hana; Condon, Ciarán; Krásný, Libor (The EMBO journal, 2020)
RNase J1 is the major 5'-to-3' bacterial exoribonuclease. We demonstrate that in its absence, RNA polymerases (RNAPs) are redistributed on DNA, with increased RNAP occupancy on some genes without a parallel increase in transcriptional output. This suggests that some of these RNAPs represent stalled, non-transcribing complexes. We show that RNase J1 is able to resolve these stalled RNAP complexes by a "torpedo" mechanism, whereby RNase J1 degrades the nascent RNA and causes the transcription complex to disassemble upon collision with RNAP. A heterologous enzyme, yeast Xrn1 (5'-to-3' exonuclease), is less efficient than RNase J1 in resolving stalled Bacillus subtilis RNAP, suggesting that the effect is RNase-specific. Our results thus reveal a novel general principle, whereby an RNase can participate in genome-wide surveillance of stalled RNAP complexes, preventing potentially deleterious transcription-replication collisions.
Keywords: genetická transkripce; DNA řízené RNA-polymerasy; messenger RNA; Bacillus subtilis; DNA-Directed RNA Polymerases; RNAP; Transcription, Genetic; torpedo; bakteriální RNA; bakteriální proteiny; exoribonukleasy; regulace genové exprese u bakterií; RNase J1; transcription-replication collision; RNA, Messenger; Gene Expression Regulation, Bacterial; Bacterial Proteins; Exoribonucleases; RNA, Bacterial; stalling